Discriminant analysis for valuing voluntary work among university youth in the United Arab Emirates - Aboutaleb, Amoura Hassan; Alazab, Ashraf Mohamed; Nser, Khaled Khamis; AL-Tkhayneh, Khawlah Mitib; Al Ali, Ahmed Abdullah (Edelweiss Applied Science and Technology, 2024)
This study aimed at identifying the extent to which university youth value voluntary work by using discriminant analysis to compare two groups of people who value and who don’t value voluntary work according to a number of variables, referred to as discrimination variables. The study sample consisted of 250 male and female students from social departments in some universities in the United Arab Emirates, where an electronic questionnaire was distributed to the sample individuals. The results revealed that most male and female university students generally value voluntary work, and that there was a significant difference between the study groups in most independent variables, except for the variable of monthly income of the youth or their families. Discrimination variables accounted for 44.6% of variance between the two groups, with Wilks’ Lambda (λ) =0.554. The percentage of the right classification of those who value and who don’t value voluntary work was 88%. The results of (Tau) value revealed that the respondents with positive attitudes towards voluntary work who have a good social and health status, good educational level, a younger age, higher affiliation and citizenship, good economic status, and belong to larger families agree with the opinion stating that the university youth in the United Arab Emirates value voluntary work with a percentage of 76%. The study concluded with a number of recommendations.